2013
DOI: 10.1097/tp.0b013e31828555d0
|View full text |Cite
|
Sign up to set email alerts
|

Low Exercise Tolerance Correlates With Reduced Inspiratory Capacity and Respiratory Muscle Function in Recipients With Advanced Chronic Lung Allograft Dysfunction

Abstract: Heterogeneity of patients with advanced lung allograft dysfunction regarding exercise tolerance might result from altered IC and impaired respiratory muscle function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…Indeed, in patients with CLAD, low exercise capacity has been associated with decreased inspiratory capacity, which may be secondary to air trapping and hyperinflation (increased residual volume) and/or restrictive lung disease (decreased TLC); as is seen in either BOS or RAS, respectively (19). Impaired respiratory muscle function was also shown to decrease exercise capacity in CLAD (19), yet in the current study, the worse functional exercise capacity in the placebo is probably not due an increase in steroid myopathy since we previously documented that the use of steroids during the initial 2 years after LTx was similar between both groups (13).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, in patients with CLAD, low exercise capacity has been associated with decreased inspiratory capacity, which may be secondary to air trapping and hyperinflation (increased residual volume) and/or restrictive lung disease (decreased TLC); as is seen in either BOS or RAS, respectively (19). Impaired respiratory muscle function was also shown to decrease exercise capacity in CLAD (19), yet in the current study, the worse functional exercise capacity in the placebo is probably not due an increase in steroid myopathy since we previously documented that the use of steroids during the initial 2 years after LTx was similar between both groups (13).…”
Section: Discussionmentioning
confidence: 99%
“…Belloli and Sato suggested that TLC and FVC were not directly comparable in defining a restrictive CLAD phenotype, as reduced survival among those with FVC <80% BL at CLAD onset could result from various factors . FVC decline may result from FEV1 loss due to hyperinflation or pathologic respiratory muscle function . Correlations between TLC and FVC were weak and suggested that TLC data were more reliable in defining restriction .…”
Section: Discussionmentioning
confidence: 99%
“…A declining FVC could also be attributable to air trapping and hyperinflation, which are the hallmarks of airflow limitation. 22,29 Subsequent studies have validated the association of FVC loss with poor survival after the onset of CLAD in independent cohorts of bilateral LTx recipients, and also extended these observations for the first time to a multicenter cohort of single LTx recipients. 20,30 Together, these studies support the idea that, whenever TLC data are not available, a decline in FVC at CLAD diagnosis is a useful clinical tool to identify LTx patients at risk for poor clinical outcomes at the onset of CLAD and during follow-up.…”
Section: Physiology Of Rasmentioning
confidence: 91%